'Neoliberal motherhood': Workplace lactation and changing conceptions of working motherhood in the contemporary US. (December 2014) - Boyer, Kate
Through an analysis of policy texts, population statistics, and the popular press, this article advances knowledge about working motherhood in the contemporary US and proposes a refinement to how wage-work/care-work relations are conceptualised. I focus on the Patient Protection and Affordable Care Act of 2011 which grants certain rights and protections to women seeking to combine lactation with wage-work. I argue that this policy represents a form of work–life integration that is particularly burdensome for working mothers, and that expectations relating to working motherhood in the contemporary US are being reshaped around the demands of neoliberalism, producing what I term 'neoliberal motherhood'. I assert that this policy represents a way of combining wage-work and care-work that is not captured within existing conceptualisations, and suggest that a re-working of theory in this area is needed to address cases in which embodied care-work is enfolded within the time and space of wage-work.